Factors of Dynamics of ICT Services Exports: The Case of Kazakhstan - V. Yu. Dodonov (Евразийская интеграция: экономика, право, политика, 2024)
The paper examines the trends in Kazakhstan’s export of information and communication technology services, which is currently one of the priorities of the country’s economic development.Aim and Tasks. Determining the impact of government spending, foreign investment and other significant factors on exports of ICT services; assessing the extent of this impact.Methods. Evaluation of the impact on the dynamics of ICT services export on the basis of comparative and correlation analysis, comprehensive analysis of the industry development indicators in the context of its export orientation, assessment of the impact on ICT services export of the factor of migration of companies and specialists from Russia in 2022–2023 and the resulting growth in the number of ICT sector enterprises with foreign capital.Results. It has been revealed that the influence of traditional factors on the export of ICT services by Kazakhstan, including state budget expenditures, gross inflow of foreign investments, and FDI stock in industries producing these services, has been insignificant or absent over the past decade. The maximum impact on the export of ICT services was caused by an increase in the presence of companies in the industry with the participation of foreign, primarily Russian capital, which occurred in 2022–23.Conclusions. The development of foreign trade activities in sectors of the economy with low initial indicators of export orientation may be more strongly influenced by non-traditional sporadic factors, such as migration of businesses and specialists in the case of the ICT sector in Kazakhstan, whereas traditional factors of their development, including government fostering and foreign investment may not be effective enough.